Adélie penguin dietary remains reveal Holocene environmental changes in the western Ross Sea (Antarctica) - Lorenzini, Sandra; Baroni, Carlo; Baneschi, Ilaria; Salvatore, Maria Cristina; Fallick, Anthony E.; Hall, Brenda L. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Carbon and nitrogen stable isotope analyses were performed on modern and Holocene Adélie penguin guano samples collected from ornithogenic soils along the Scott Coast (Southern Victoria Land, Antarctica), from Cape Irizar to Dunlop Island, and at Cape Bird (Ross Island). Guano samples also were sieved and sorted under stereomicroscope in order to select penguin dietary remains, such as fish bones and otoliths. Carbon and nitrogen stable isotope composition, coupled with the taxonomic identification of fish otoliths from Scott Coast Holocene samples, indicated a mainly fish-based diet for this area, with Pleuragramma antarcticum as the most eaten prey throughout the investigated period (from 390 cal BP to ca 7300 cal BP). The isotopic values of Ross Island samples (from modern to 3850 cal BP) showed a krill consumption increase in the samples younger than 2000 cal BP, with the maximum in modern samples. Scott Coast and Ross Island Holocene samples showed δ13C and δ15N trends similar to those previously published from Terra Nova Bay (northern Victoria Land), whereas modern samples from Ross Island have similar δ15N composition but different δ13C values. This δ13C divergence started at ca 2000 BP and follows the abandonment of the Scott Coast colonies. The δ13C trend observed in Ross Island and Terra Nova Bay samples and the abandonment of the Scott Coast colonies could suggest the stability and the persistence of the previous oceanographic conditions (i.e. polynya) for the Terra Nova Bay area and the establishment of new conditions for water circulation in the Southern Ross Sea since ~ 2000 BP when persistent sea-ice sealed the Scott Coast.
id: 2347